Structure of Human J-type Co-chaperone HscB Reveals a Tetracysteine Metal-binding Domain - Bitto, Eduard; Bingman, Craig A.; Bittova, Lenka; Kondrashov, Dmitry A.; Bannen, Ryan M.; Fox, Brian G.; Markley, John L.; Phillips, George N. (The Journal of biological chemistry, 2008)
Iron-sulfur proteins play indispensable roles in a broad range of biochemical processes. The biogenesis of iron-sulfur proteins is a complex process that has become a subject of extensive research. The final step of iron-sulfur protein assembly involves transfer of an iron-sulfur cluster from a cluster-donor to a cluster-acceptor protein. This process is facilitated by a specialized chaperone system, which consists of a molecular chaperone from the Hsc70 family and a co-chaperone of the J-domain family. The 3.0Å crystal structure of a human mitochondrial J-type co-chaperone HscB revealed an L-shaped protein that resembles Escherichia coli HscB. The important difference between the two homologs is the presence of an auxiliary metal-binding domain at the N terminus of human HscB that coordinates a metal via the tetracysteine consensus motif CWXCX9–13FCXXCXXXQ. The domain is found in HscB homologs from animals and plants as well as in magnetotactic bacteria. The metal-binding site of the domain is structurally similar to that of rubredoxin and several zinc finger proteins containing rubredoxin-like knuckles. The normal mode analysis of HscB revealed that this L-shaped protein preferentially undergoes a scissors-like motion that correlates well with the conformational changes of human HscB observed in the crystals.